Interaction of metal dust adhered on castellated substrates with the ELMy H-mode plasmas of ASDEX-Upgrade. (13th August 2018) - Ratynskaia, S.; Tolias, P.; De Angeli, M.; Rohde, V.; Herrmann, A.; Ripamonti, D.; Riva, G.; Thorén, E.; Vignitchouk, L.; Sieglin, B.; Krieger, K.; Neu, R.
Abstract: Castellated substrates with adhered micron dust have been exposed in the outer ASDEX-Upgrade divertor to ELMy H-mode discharges. Beryllium proxy (chromium, copper) and refractory metal (tungsten, molybdenum) dust has been deposited on the plasma-facing and plasma-shadowed sides of the monoblocks as well as the bottom of the gaps. Interaction with time-averaged transient heat loads up to 5 MW m −2 led to dust remobilization, clustering, melting and wetting-induced coagulation. The amount of dust released in the vessel has been quantified and remobilized dust trajectories inferred. Gaps can efficiently trap locally adhered dust, but dust detaching from adjacent monoblocks does not preferentially move inside the gaps implying that they do not constitute a dust accumulation site. Heat transfer simulations of melting events are also reported taking into account heat constriction due to the finite contact area and the presence of surface roughness.